Genomic, Proteomic, and Phenotypic Spectrum of Novel O-Sialoglycoprotein Endopeptidase Variant in Four Affected Individuals With Galloway-Mowat Syndrome - Ali Alghamdi, Malak; Benabdelkamel, Hicham; Masood, Afshan; Saheb Sharif-Askari, Narjes; Hachim, Mahmood Y.; Alsheikh, Hamad; Hamad, Muddathir H.; Salih, Mustafa A.; Bashiri, Fahad A.; Alhasan, Khalid; Kashour, Tarek; Guatibonza Moreno, Pilar; et al. (Frontiers in Genetics, 2022)
Galloway-Mowat syndrome is a rare autosomal recessive disease characterized by a unique combination of renal and neurological manifestations, including early-onset steroid-resistant nephrotic syndrome, microcephaly, psychomotor delay, and gyral abnormalities of the brain. Most patients die during early childhood. Here, we identified a novel homozygous O-sialoglycoprotein endopeptidase (OSGEP) variant, c.973C>G (p.Arg325Gly), in four affected individuals in an extended consanguineous family from Saudi Arabia. We have described the detailed clinical characterization, brain imaging results, and muscle biopsy findings. The described phenotype varied from embryonic lethality to early pregnancy loss or death at the age of 9. Renal disease is often the cause of death. Protein modeling of this OSGEP variant confirmed its pathogenicity. In addition, proteomic analysis of the affected patients proposed a link between the KEOPS complex function and human pathology and suggested potential pathogenic mechanisms.